Determination of the factors that influence customer satisfaction of banking services in the city of Guayaquil - Abarca, Erick; Acosta, Andrea; Bajaña, Yanina (Revista Universidad de Guayaquil, 2020)
The objective of this research is to examine the quality with which services are provided in thefinancial sector of the city of Guayaquil, for this purpose an analysis of the factors that affectcustomer satisfaction with banking services is proposed, in this way it is intended Recognize themost relevant constructs while trying to know a measurement tool. To begin with, a thorough literature review related to basic theories such as SERVQUAL, SERVPERF and BankServ iscarried out in order to build a tool that helps to measure customer satisfaction, this is done throughdescriptive statistics and correlational of the collected data. The research allows us to concludethat there are four factors that positively influence the satisfaction of clients of Guayaquil bankingservices: quality of service, environment, accessibility and the financial factor.
Keywords: Satisfaction; customers; factors; incidence; banking services